Analysis of the Fulfillment of Labor Social Security as a Work of Legal Protection - Siti Ummu Adillah; Amin Purnawan (Journal of Morality and Legal Culture, 2020)
The research objective is to analyze the fulfillment of labor social security as a form of legal protection for workers in the formal and informal sectors as well as barriers and their solutions. The juridical normative research method is descriptive analysis. The statutory approach method (statue approach). By using secondary data, which is supported by primary data, in the form of interviews with informants. The analysis technique uses qualitative analysis methods. The results showed that the fulfillment of employment social security for workers in the formal sector, namely the company is obliged to register its employees. Meanwhile, workers in the informal sector must pay their dues independently, be borne by themselves, because they work independently and the guarantee program that must be followed is only the work accident insurance and death insurance programs. Obstacles for workers in the formal sector are many companies that are “mischievous” and dishonest, there is manipulation of their salary report, companies are late in paying dues, and the supervisory function is not working properly